Analysis of packaging quality control of PT. LMN using the seven tools method and new seven tools - Permana, Handy Natan; Saifuddin, Joumil Aidil (Universitas Mercu Buana, 2024)
Product quality is a crucial factor that influences success in the market and in the company's production process. Quality products meet company standards and consumer expectations. The aim of this study is to identify the causes of product rejections and to analyze process improvements in terms of man, material, machine, method, measurement, and environment to reduce product rejections. The results of data collection show the dominant types of rejects, with the following proposed improvements: Maintain the operators' jobdesk so that they become experts in one area, by motivating them through rewards to improve work quality. Ensure spare stock, efficient forklift lanes and H-1 glue communication. Make continuous improvements in every part of the packaging department and build an information system for glue type requirements. Place SOPs in a visible and obvious location, add machine filters near operators, and improve machines to prevent overweight/underweight rejects. Check and calibrate machines regularly, implement scheduled machine maintenance checklists, and standardise maintenance and delegate tasks to optimise staff schedules. Regularly update the parts list according to the machine specifications, make a tool to pour glue from the drum with minimal noise, and perform regular machine maintenance and use bearings to reduce vibration.